Central Hemodynamic Function in Miners with Thermal Injury - V. V. Moroz; Yu. A. Churlyaev; A. V. Sherstobitov; V. Ya., Martynenkov; L. Yu. Redkokasha; P. G. Sitnikov; N. V. Kolyshkina (Общая реаниматология, 2008)
Objective: to study the specific features of central hemodynamic function in the acute phase of severe thermal injury (STI) in miners who had a length of service of 10 years or more. Subjects and methods. A noninvasive study of central hemodynamics was conducted in 33 miners with severe thermal injury (a study group) and 34 patients without a length of underground work who had the same condition (a control group). Both groups were matched by age and the nature and severity of thermal injuries. Central hemodynamics was evaluated by the following parameters: mean arterial blood, heart rate, stroke index (SI), cardiac index (CI), cardiac output (CO), specific vascular peripheral resistance (SVPR) determined by Cubichek tetrapolar rheography. Results. The study indicated that on posttraumatic days 3—7, as compared with victims without a length of underground service, the miners had more pronounced central hemodynamic changes: decreases in CI, SI, and CO and an increase in SVPR. In the control group, from day 3, the hemodynamic changes were the following: increases in SI, SI, and CO and a decrease in SVPR. In the miners, the above features were attributable to the baseline central hemodynamic function. Conclusion. Thus, unlike the victims without a length of underground service, the miners with severe thermal injury develop more significant and prolonged central hemodynamic disorders. The detected differences during thermal injury are determined by the lowered reserve capacities of the cardiovascular system in miners due to the long-term exposure to poor working conditions, i. e. an underground service length of 10 years or more. Key words: thermal injury, miner, hemodynamics, type of circulation.